Hubungan Tingkat Pengetahuan Kesehatan Reproduksi Remaja Putri dengan Perilaku Menstrual Hygiene - Sambeang Putra, Melati Oktaviani; Dhinny Novryanthi; Eva Martini (Jurnal Ventilator, 2024)
Knowledge refers to a person's understanding or knowledge of a subject gained via experience or study. The definition of reproductive health is a condition of well-being in which people are neither ill or disabled and have access to reproductive health information, aid, and education. Good menstrual hygiene is essential for preventing pain and infection during the menstrual cycle. This study aims to determine the relationship between the level of reproductive health knowledge of adolescent girls with menstrual hygiene behavior. This research method uses quantitative methods with a Cross Sectional approach, using a questionnaire with Simple Random Sampling data collection with a total of 61 respondents. The Chi Square test (P = 0.000 < ? = 0.05) indicates a significant link between teenage girls' reproductive health knowledge and menstrual hygiene behavior at SMP Negeri 5 Sukabumi City. H? is accepted while H0 is rejected. The absence of a significant relationship between reproductive health knowledge of adolescent girls and menstrual hygiene. This work has the potential to enhance school policy, increase knowledge about menstrual hygiene and reproductive health, benefit young women, and open up new avenues for future research.